Saliva, Plasma, and Multifluid Metabolomic Signatures of Periodontal Disease, Type 2 Diabetes Progression, and Markers of Glycemia and Dyslipidemia Among Puerto Rican Adults With Overweight and Obesity - Zicheng Wang; Danielle E. Haslam; Caleigh M. Sawicki; Sona Rivas‐Tumanyan; Frank B. Hu; Liming Liang; David T. W. Wong; Kaumudi J. Joshipura; Shilpa N. Bhupathiraju (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Evidence from cohort studies indicates a bidirectional relationship between periodontal disease and type 2 diabetes (T2D), but the underlying mechanisms remain unknown. In this study, we aimed to (1) identify saliva, plasma, and multifluid metabolomic signatures associated with periodontal disease and (2) determine if these signatures predict T2D progression and cardiometabolic biomarkers at year 3. Methods and Results We included participants from the SOALS (San Juan Overweight Adult Longitudinal Study) (n=911). Metabolites from saliva (k=635) and plasma (k=1051) were quantified using liquid chromatography–mass spectrometry. We applied elastic net regression with 10‐fold cross‐validation to identify baseline metabolomic signatures of periodontal disease. Multivariable Cox proportional hazards regression and linear regression were used to evaluate the association with T2D progression and biomarker concentrations. Metabolomic profiles included highly weighted metabolites related to lysine and pyrimidine metabolism. Periodontal disease or its 3 metabolomic signatures were not associated with T2D progression in 3 years. Prospectively, 1‐SD increments in the multifluid and saliva metabolomic signatures were associated with higher low‐density lipoprotein (multifluid: 12.9±5.70, P=0.02; saliva: 13.3±5.11, P=0.009). A 1‐SD increment in the plasma metabolomic signature was also associated with Homeostatic Model Assessment for Insulin Resistance (2.67±1.14, P=0.02) and triglyceride (0.52±0.18, P=0.002). Conclusions Although metabolomic signatures of periodontal disease could not predict T2D progression, they were associated with low‐density lipoprotein, triglyceride, and Homeostatic Model Assessment for Insulin Resistance levels at year 3.